Multivariate Analysis of the Organic Acid Content of Gouda type Cheese during Ripening - Califano, Alicia Noemi (2000)
Gouda cheeses from a local plant were subjected to different ripening conditions and analyzed. The effects of ripening temperature, type of packaging film and storage period before packaging on the organic acids content of Gouda cheese were studied. A factorial design of 23×5 was used, where the three factors selected in two levels were: (1) time of storage before packaging, 4 and 10 days, (2) ripening temperature, 10 and 20°C, and (3) plastic film (BK1 and BK5; Grace, Argentina). Ripening time was the fourth factor considered; sampling times were 15, 25, 35, 49 and 70 days after production. At the beginning of the experiment (4 days of ripening), mean water content of samples was 44.0±0.9%. At 70 days of ripening, humidities were 39.7±0.6 and 40.8±0.6% for cheeses stored at 20 and 10°C, respectively. Nine organic acids (formic, orotic, uric, lactic, acetic, citric, pyruvic, propionic and butyric) were analyzed in each sample by HPLC. Samples of the same batch with four days of ripening and cheeses traditionally ripened (without packaging) were also studied. None of the factors affected the orotic and uric acid concentrations and butyric acid was not detected in any sample. The remaining acids content increased linearly with ripening time. Increasing storage temperature accelerated the maturation processes. The corresponding Q10for each acid was calculated as the ratio between the rate of increase at 20 and 10°C, obtaining values between 1.2 and 5.8. Three PCA factors interpreted 87% of the total variation in the samples. Discriminant analysis classified cheeses according to their age.